1994
DOI: 10.1073/pnas.91.9.3931
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophilin B trafficking through the secretory pathway is altered by binding of cyclosporin A.

Abstract: Cyclophilin B is targeted to the secretory pathway via an endoplasmic reticulum signal sequence. We analyzed the localization and trafficking of endogenous and transfected cyclophilin B in mammalian cells. Cyclophilin B accumulates both in the endoplasmic reticulum and in complexes on the plasma membrane. The immunosuppressant cyclosporin A specifically mobilizes cyclophilin B from the endoplasmic reticulum, and promotes the secretion of cyclophilin B into the medium. We suggest that cyclosporin A competes wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
103
1
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(120 citation statements)
references
References 52 publications
14
103
1
1
Order By: Relevance
“…Cyp B contains N-terminal signal sequence (21), is produced in endoplasmic reticulum, and is secreted into biological fluids such as milk and plasma (34,35). Spik and his colleagues demonstrated that peripheral blood T lymphocytes possess binding sites of Cyp B that internalize extracellular Cyp B into cells (36).…”
Section: Discussionmentioning
confidence: 99%
“…Cyp B contains N-terminal signal sequence (21), is produced in endoplasmic reticulum, and is secreted into biological fluids such as milk and plasma (34,35). Spik and his colleagues demonstrated that peripheral blood T lymphocytes possess binding sites of Cyp B that internalize extracellular Cyp B into cells (36).…”
Section: Discussionmentioning
confidence: 99%
“…Two of those, namely Cyp18 and Cyp23, belong to the cyclophilin family of PPIases. As Cyp18 was preferably found in the cytoplasm and the nucleus (Marks et al, 1991) whereas Cyp23 resides in the endoplasmic reticulum (Price et al, 1994), we focused our further analysis on potential Cyp18-p53 interactions. CoIP experiments revealed a Cyp18 association with p53 in both the cytoplasmic and nuclear fractions as shown by LC-ESI-MS/MS analysis ( Figure 1a, sections a and b).…”
Section: Physical Association Of P53 With Cyp18mentioning
confidence: 99%
“…CypB is a member of the larger immunophilin family of cis-trans peptidyl-prolyl isomerases, which also includes the FK506 binding proteins and target of rapamycin (Tor) (25). CypB has been observed in the ER and nucleus and can be found in appreciable levels in blood (150 ng͞ml) and breast milk (26,27). Whereas its role as a chaperone in protein transport through the ER (28) or as a costimulatory molecule for T lymphocytes (29) has been speculated upon, the exact function of CypB has remained uncertain.…”
mentioning
confidence: 99%